2021
DOI: 10.1042/bsr20211790
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Campylobacter jejuni and Salmonella typhimurium in chicken using PCR for virulence factor hipO and invA genes (Saudi Arabia)

Abstract: C. jejuni and S. typhimurium are the leading causes of bacterial food contamination in chicken carcasses. Contamination is particularly associated with the slaughtering process. This study isolated C. jejuni and S. typhimurim from fifty chicken carcass samples, all of which were acquired from different companies in Riyadh, Saudi Arabia. The identification of C. jejuni was performed phenotypically by using a hippurate test and genetically using a polymerase chain reaction with primers for 16S rRNA and hippurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
0
4
1
1
Order By: Relevance
“…The findings from this baseline study provide the first published investigation on the status of Campylobacter in chilled chicken meat sold in supermarkets in the UAE. Lower recovery of Campylobacter in chicken carcasses was observed in our study (28.6%) compared to results from neighboring countries, such as Qatar (36.5%) and Saudi Arabia (52.2%) (Abu-Madi et al 2016;Alarjani et al 2021). In this study, 71.4% of the tested chicken carcasses were contaminated with Campylobacter at a level below 1 log 10 CFU/g (the quantification limit for the designated direct plating method).…”
Section: Overall Campylobacter Recovery and Enumerationcontrasting
confidence: 64%
“…The findings from this baseline study provide the first published investigation on the status of Campylobacter in chilled chicken meat sold in supermarkets in the UAE. Lower recovery of Campylobacter in chicken carcasses was observed in our study (28.6%) compared to results from neighboring countries, such as Qatar (36.5%) and Saudi Arabia (52.2%) (Abu-Madi et al 2016;Alarjani et al 2021). In this study, 71.4% of the tested chicken carcasses were contaminated with Campylobacter at a level below 1 log 10 CFU/g (the quantification limit for the designated direct plating method).…”
Section: Overall Campylobacter Recovery and Enumerationcontrasting
confidence: 64%
“…Data from surveillance studies in different countries indicated a high prevalence of Campylobacter on raw retail chicken meat. For example, Campylobacter was detected in 28.6%, 36.5%, 41.2% and 52.2%, 59.9% of samples from chicken meat from retail stores in the United Arab Emirates, Qatar, the United Kingdom, Saudi Arabia, and Canada, respectively [ 187 , 188 , 189 , 190 , 191 ]. It is estimated that a reduction in Campylobacter counts in the neck and breast skin to 10 3 CFU/g reduces the public health risk by 50% [ 192 ].…”
Section: Post-harvest Control Measures (Production Chain Interventions)mentioning
confidence: 99%
“…Typhi strain 3N4 dengan tingkat percent coverage sebesar 99%. Alarjani et al (2021) melaporkan berdasarkan hasil BLAST terdeteksi cemaran Salmonella Enterica subs in the enterica ser Typhimurium dan Salmonella Spp (Ladunga, 2009) Aplikasi fungsi 1 pada penelitian Salmonella memiliki parameter penting yang mempengaruhi hasil BLAST diantaranya yaitu menentukan gen target berdasarkan dugaan serovar (Madden, 2013), data query sequence, reference sequence. Langkah awal yang dibutuhkan dalam menentukan gen target adalah memilih urutan basa spesifik yang banyak ditemukan pada spesies tersebut dan tidak ada pada bakteri lain.…”
Section: Hasil Dan Pembahasanunclassified